Media Improvisation of Lecturers in the State-Owned Colleges of Education in the South-West, Nigeria - Omoike, Adenike Damilola; Oyeyemi Ogunwuyi, Babatunde (International Journal of Knowledge Content Development & Technology, 2022)
Media improvisation among lecturers in colleges is inevitable because of insufficient media resources for utilization. The study investigated media improvisation in the state -owned colleges of education in the South-West, Nigeria. The study is anchored on Media Richness Theory. Stratified sampling technique was adopted to select 812 lecturers. Media improvisation scale (r = .71) was used for data collection and T-test statistical method was adopted for data analysis. The result showed that there was no significant differences between media improvisation of Art/Social Science and Science lecturers (Crit – t = 1.96, Cal. t = 821, df = 278, p>.05) and that of lecturers in the School of Art/Social Sciences and Vocational/Technical Education (Crit. t = 1.96, Cal. t = .136, df = 276, p>.05). Significant difference did not exit between that of the Schools of Languages and Education (Crit. t = 1.96, Cal. t = 1.946, dif. = 288 p<.05) . It is recommended that media improvisation of lecturers in schools should be encouraged and improved upon.